Characterization of Enterobacterales growing on selective CPE screening plates with a focus on non-carbapenemase-producing strains - Reut Efrati Epchtien; Elizabeth Temkin; Mor N. Lurie-Weinberger; Ophir Kastel; Alona Keren-Paz; David Schwartz; Yehuda Carmeli (Microbiology Spectrum)
ABSTRACT Carbapenem-resistant Enterobacterales (CRE) are divided into two distinct groups: carbapenemase-producing (CPE) and non-carbapenemase-producing (non-CPE). The population of non-CPE growing on CPE selective plates during routine screening is usually not reported and is not well defined. This study aimed to characterize non-CPE isolates growing on those plates. Isolates were collected from two medical institutions in Israel between May and November 2022. Species identification and antibiotic susceptibility testing were performed using VITEK systems. Further analyses focused on Klebsiella pneumoniae and Escherichia coli which were the most common isolates. Meropenem MIC was determined by E-test. Fourier-transform infrared spectroscopy (FTIR) was used to analyze phenotypic similarity, and whole genome sequencing was conducted on a subset of non-CPE isolates. Of 260 isolates growing on selective CPE screening plates, 60.4% were non-CPE. The most common non-CP isolates were K. pneumoniae (65.6%) followed by E. coli (20.4%). Of the non-CP K. pneumoniae and E. coli isolates, 78.2% were susceptible to meropenem. All non-CP K. pneumoniae and E. coli isolates were multidrug-resistant (MDR) and belonged to multiple FTIR clusters. The 21 sequenced non-CPE isolates carried multiple mechanisms of resistance. Isolates had multiple beta-lactamases and all had penicillin-binding protein modifications and porin mutations; in meropenem-resistant K. pneumoniae isolates, both Ompk35 and Ompk36 were mutated. The majority of isolates growing on selective CPE screening plates are non-CPE but are MDR. Laboratory reporting of these MDR bacteria might be useful for guiding treatment and prophylaxis when indicated, as well as for infection control.IMPORTANCESelective screening plates for carbapenemase-producing Enterobacterales (CPE) are used to detect CPE carriers for infection control purposes. We characterized non-CPE isolates that grew on selective CPE screening plates, which are intended to filter them out. We found that 60% of isolates that grew on these plates were not CPE. They included both meropenem-susceptible and meropenem-resistant isolates and were multidrug-resistant with multiple resistance mechanisms. These test results, which are usually not reported by laboratories, may be clinically valuable.